Starch granule morphology in oat endosperm. (January 2017) - Saccomanno, Benedetta; Chambers, Alan H.; Hayes, Alec; Mackay, Ian; McWilliam, Simon C.; Trafford, Kay
Abstract: Mature and developing oat ( Avena sativa ) grains were sectioned and image analysis methods used to estimate the starch granule-size distribution and morphology in endosperm cells. This showed that oat endosperm cells contain two types of starch granule: compound starch granules such as those seen in rice endosperm and in most other grasses; and simple granules similar to the B-type starch granules seen in the endosperm of Triticeae species such as wheat ( Triticum aestivum ). The simple granules in oats are similar in size and relative abundance to B-type granules in Triticeae suggesting that they may share a common evolutionary origin. However, there is a fundamental difference between oats and Triticeae in the timing of granule initiation during grain development. In Triticeae, the B-type granules initiate several days after the A-type granules whereas in oats, both the simple and compound granule types initiate at the same time, in early grain development. Highlights: As in Triticeae species, oats ( Avena sativa ) have a bimodal starch granule-size distribution. Oat grains contain both large compound starch granules and small simple granules. In oats, there are no A-type starch granules like those in Triticeae species. The small granules in oats look like the B-type granules in Triticeae starch. In developing oat grains, both types of starch granule initiate at the same time.